The Problem Of Enhancing The Role Of The Teacher In Modern Armenian Society - Minasyan, Nelli; Smbatyan, Srbuhi (ՀՀ ԳԱԱ)
Developments in the 21st century demand new approaches in the field of education, at the center of which is the teacher. The model of the teacher-pedagogue, where the teacher was a transmitter of knowledge, has currently exhausted itself. On the other hand, the master teacher model is developing in the world, which primarily implies the formation of abilities and skills in students, which in turn will allow them to acquire knowledge independently. The adoption of this model will, on the one hand, ensure the effectiveness of educational reforms, and on the other hand, will raise the role of the teacher in Armenian society.
Keywords: Հայագիտություն; Հայոց պատմություն; Պատմություն; Հայոց ցեղասպանություն (1915); Հայագիտական ժառանգություն; Հնագիտություն և ազգագրություն; Փիլիսոփայություն և իրավունք; Արվեստ և ճարտարապետություն; Ժողովրդագրություն և կառավարում